Exploring the Role of Caspase-3 and IL32 in SARS-CoV-2 Infection among Iraqi Patients - Abed Alhussien, Thaer A.; Fadhil , Hula Y. (Iraqi Journal of Science, 2023)
Understanding Caspase-3 (CASP-3) and interleukin-32 (IL32) roles in SARS-CoV-2 infection is critical to linearize the pathogenesis of the virus as well as the resultant disease which may uncover novel therapeutic targets in treating COVID-19 patients. This study aimed to evaluate caspase‐3 (CASP3) and interleukin 32 (IL32) roles and their correlation with the disease severity among patients. The case-control study (140 patients and 60 healthy controls) was performed with molecular and ELISA assays. CASP3 and IL32 serum levels were determined along with other clinical data of patients. CASP3 levels were classified as significantly higher (p < 0.001), while IL-32 levels were significantly lower in production (p < 0.001) in most critical and severe patients compared with mild-moderate. Additionally, IL 32 production reduced with older age, whereas CASP3 levels elevated with older age compared to younger years. Also, the IL-32 showed a protective factor from the severity of the SARS-CoV-2 progression as a negative correlation with the biomarkers (lactate dehydrogenase (LDH), ferritin and D. dimer) values. Thus, IL-32 appeared as the opposite effect of the CASP3 on the severity of COVID-19 infections. ROC curve analysis indicated that IL32 is a good predictor in providing information about the severity of the disease and host recovery. Whereas CASP3 is associated with progressive disease (cut-off value = 160.7 pg/mL; 5.64 ng/mL respectively). CASP3 and IL32 can possibly provide information about the COVID-19 and could be used as cytokine markers to detect SARS-CoV2 infection severity and determine the most reliable treatment plan. More research is needed on this subject. Keywords: Autoimmune disease; Hematological disorder; Renal failure; Inflammatory markers.